Regulation of Oxidative Stress in Corneal Endothelial Cells by Prdx6 - Matthew Lovatt; Khadijah Adnan; Gary S. L. Peh; Jodhbir S. Mehta (MDPI AG, 2018)
The inner layer of the cornea, the corneal endothelium, is post-mitotic and unable to regenerate if damaged. The corneal endothelium is one of the most transplanted tissues in the body. Fuchs’ endothelial corneal dystrophy (FECD) is the leading indication for corneal endothelial transplantation. FECD is thought to be an age-dependent disorder, with a major component related to oxidative stress. Prdx6 is an antioxidant with particular affinity for repairing peroxidised cell membranes. To address the role of Prdx6 in corneal endothelial cells, we used a combination of biochemical and functional studies. Our data reveal that Prdx6 is expressed at unusually high levels at the plasma membrane of corneal endothelial cells. RNAi-mediated knockdown of Prdx6 revealed a role for Prdx6 in lipid peroxidation. Furthermore, following induction of oxidative stress with menadione, Prdx6-deficient cells had defective mitochondrial membrane potential and were more sensitive to cell death. These data reveal that Prdx6 is compartmentalised in corneal endothelial cells and has multiple functions to preserve cellular integrity.